Towards National Consensus: Spiritual Care in the Australian Healthcare Context - Holmes, Cheryl (Religions, 2018)
The Enhancing Quality and Safety: Spiritual Care in Health National Consensus Conference brought together key stakeholders from across Australia to agree a national framework to ensure quality and safety in spiritual care services through a nationally consistent approach to the provision of spiritual care in Australian hospitals. A working group planned the conference that was held over two days. Invitations were distributed to a wide range of stakeholders to ensure a diversity of voices contributed to the outcomes. The conference proceedings included presentations, small group work and facilitated discussion to enable progress on the conference objective. A conference report of the key outcomes was produced and widely distributed. The national consensus conference outcomes described five principles for the design and delivery of spiritual care services for the Australian context. Ten policy statements described key deliverables that could be used to benchmark and measure a nationally consistent approach to spiritual care.